THE INFLUENCE OF SEMANTIC INTEGRATION ON READING PROFICIENCY OF 6TH SEMESTER STUDENTS AT MUHAMMADIYAH TANGERANG UNIVERSITY: A CASE STUDY ON THE NOVEL “THE STRANGE CASE OF DR. JEKYLL AND MR. HYDE” - Aidil Syah Putra; Alvita Farha A; Kukuh Satria (Media Inovasi Pendidikan dan Publikasi, 2024)
This study investigates the influence of semantic integration on the reading proficiency of 6th-semester students at Muhammadiyah Tangerang University, focusing on the novel